2002
DOI: 10.1111/j.1834-7819.2002.tb00318.x
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Dental and Oral Trauma in South‐East Queensland During 1998

Abstract: Background: This project investigated the aetiology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
33
3
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 15 publications
10
33
3
1
Order By: Relevance
“…The majority of traumatic injuries to the dentition are treated in other institutions as evidenced by another Time in hours study in the same geographic location which revealed 130 patients in the same age range as this study in one calendar year. 1 The exclusion of lip lacerations and soft tissue injuries without trauma to the dentition is partly responsible for the relatively low numbers and the disparity between this study and others of a similar population. 7,16 One and 2 year olds comprised 30 per cent of our study population which is consistent with other hospital based series, 7,11,12 and this can be compared with Wood and Freer's study of dental clinics that demonstrated a peak age group of 6-10.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The majority of traumatic injuries to the dentition are treated in other institutions as evidenced by another Time in hours study in the same geographic location which revealed 130 patients in the same age range as this study in one calendar year. 1 The exclusion of lip lacerations and soft tissue injuries without trauma to the dentition is partly responsible for the relatively low numbers and the disparity between this study and others of a similar population. 7,16 One and 2 year olds comprised 30 per cent of our study population which is consistent with other hospital based series, 7,11,12 and this can be compared with Wood and Freer's study of dental clinics that demonstrated a peak age group of 6-10.…”
Section: Discussionmentioning
confidence: 68%
“…Other leading causes are impacts with a person or object, bicycle accidents, motor vehicle accidents, sporting activities and intentional injuries, including parental abuse. 1,2,[7][8][9][10][11][12] Treatment timing guidelines have been reviewed by Andreasen et al 13 and they subdivide dento-alveolar trauma into the following groups: 1) acute treatment requirement (within three hours) -avulsion, extrusion, root fractures and alveolar fractures; 2) subacute treatment requirement (within 24 hours) -crown and crown/root fractures, intrusion, concussion, subluxation and primary tooth injuries which do not interfere with the occlusion or displace into the follicle of the permanent tooth; and 3) delayed treatment requirement (after 24 hours) -crown fractures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 5e8% of traumatic injuries involve crown and root with pulpal exposure. 2,4 Uncomplicated enamel-dentin fracture is also common. Prior studies have estimated that one out of every four persons under the age of 18 will sustain a traumatic dental injury in the form of anterior crown fracture.…”
Section: Introductionmentioning
confidence: 99%
“…7-10 yaş arası okul çağı döneminde ise sosyalleşme, çocu-ğun kendi vücudunu ve yeteneklerini tanıması ve bireysel sportif aktivitelerindeki artış ile travma görül-me oranı tekrar artmaktadır 7,11,12 . Genellikle erkek çocukların kız çocuklara oranla travmaya daha yatkın olduğu gözlenmekle birlikte 1,3,4,[13][14][15] , bazı araştırma-cılar kız çocukların da en az erkek çocuklar kadar risk taşıdığı bildirmiştir 16,17 . Sınıf II Bölüm I iskeletsel kapanış ilişkisine sahip, ağız solunumu yapan ve şiddetli üst solunum yolu rahatsızlıkları olan çocuklar travma açı-sından risk taşımaktadır 1,3 .…”
unclassified